1991
DOI: 10.3109/08958379109145289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfuric Acid on Ferret Respiratory Tract Clearance

Abstract: I NTRO D U CTI 0 NMany animal species have been successfully used as models by toxicologists in respiratory tract deposition and clearance studies. Among these are rabbits (Chen and Schlesinger, 1983;Schlesinger, 1990), dogs (Wolff et al., 1981), donkeys (Schlesinger et al., 1979), rats (Kenoyer et al., 1981;Mannix et al., 1983), sheep (Sackner et al., 1981, mice (Fairchild et al., 1975), guinea pigs , and hamsters (Harbison and Brain, 1983). When selecting an animal model for a particular clearance study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…The clearance data reported here are in good agreement with that previously reported for the normal young adult ferret (Mannix et al, 1991), and are distinctly different from the clearance patterns of rodents as reported by others (Bailey et al, 1989) and measured in our laboratory using the same methods as in the present work (Kenoyer et al, 1981;Mannix et al, 1982). Therefore, it is of limited value to compare directly the slopes found for particle clearance from the head and thoracic regions among the various species.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The clearance data reported here are in good agreement with that previously reported for the normal young adult ferret (Mannix et al, 1991), and are distinctly different from the clearance patterns of rodents as reported by others (Bailey et al, 1989) and measured in our laboratory using the same methods as in the present work (Kenoyer et al, 1981;Mannix et al, 1982). Therefore, it is of limited value to compare directly the slopes found for particle clearance from the head and thoracic regions among the various species.…”
Section: Discussionsupporting
confidence: 86%
“…The purified air-exposed group had a clearance pattern very similar to that measured in older control ferrets in a previous study (Mannix et al, 1991). As in the earlier study, about 20% of the tracer radioactivity was presumed to be deposited on slow-clearing epithelium, as evidenced by the time-zero intercept of the slow-clearing component.…”
Section: Head Region Analysissupporting
confidence: 78%
See 3 more Smart Citations